Pengaruh Bimbingan Belajar Terhadap Hasil Belajar Matematika Peserta Didik Kelas IV - Rofiatun Nisa’; Nadia Nur Fatria (IBTIDA, 2022)
The purpose of this study was to determine 1) the application of student tutoring, 2) the level of mathematics learning outcomes for fourth-grade students, 3) the effect of tutoring on fourth-grade students' mathematics learning outcomes at SDN Kembangan Sekaran Lamongan. This research is quantitative research with an experimental descriptive method, with a sample of 8 students. The instruments used are observation, documentation, and tests. Data analysis used descriptive analysis and hypothesis testing with a t-test. The results showed that: 1) the percentage of tutoring observation results 100% of students who attended tutoring, 82% of students paid attention when the teacher explained the material, 90% of students actively asked when the teacher finished explaining the material, 90% of students were able to master the task that had been given. when tutoring, 80% of students can answer questions given by the teacher during tutoring, 2) student learning outcomes for class IV obtained 62% of students are at a very high level, meaning that learning outcomes students experienced a significant increase, 3) the results obtained are t_count is greater than t_table, namely 5.036 > 2.145, meaning that there is a significant difference in the mathematics learning outcomes of fractions. This proves that this tutoring is effectively used to improve the learning outcomes of fourth-grade students at SDN Kembangan Sekaran Lamongan